Peran Muhammadiyah Dalam Toleransi Antar UmatBeragama Di Desa Bandardawung KecamatanTawangmangu Kabupaten KaranganyarPeriode 2013-2018 - Sultoni, Sultoni, Drs. M. DarojatAriyanto, M.Ag (2017)
We live in a country which is full of diversity, whether ethnic, religious, or cultural. To live in peace and harmony certainly needs tolerance tolerance. The ounderMuhammadiyah, KH Ahmad Dahlan exemplifies the open and tolerant attitude, but remains firmly in the principles of Islam.Bandardawung is a plural village in religion. in the village there are three religions namely Islam, Christianity and Buddhism. All three religions until now coexist harmoniously and almost no serious problems in relations between them The purpose of this study is to determine how Muhammadiyah role in religious tolerance in Bandardawung Tawangmangu Karanganyar district is. The type of research is a field research (field research) with a qualitative descriptive approach. The methods used in data collections are observation, interview (interview) and documentation. The descriptive analysis method is used in the analysis. From these results it can be concluded that the Muhammadiyah take an active role in creating inter-religious harmony in the village andardawung. Muhammadiyah is able to provide an example to the community how to address differences confidence in inter-religious relations. Keywords : Role, Muhammadiyah, Religius Tolerance